Feasibility and costs of a targeted cholera vaccination campaign in Ethiopia. Issue 10 (3rd October 2018) - Teshome, Samuel; Desai, Sachin; Kim, Jerome H.; Belay, Dires; Mogasale, Vittal
ABSTRACT: Shanchol™, a WHO-prequalified oral cholera vaccine (OCV), has been used to control endemic cholera in Asia, as well as in emergencies and outbreaks elsewhere. The vaccine has not been used by public health systems in cholera-endemic settings of Africa although several outbreak response campaigns have been conducted. Here we present experiences from a mass vaccination campaign in a cholera-endemic setting of Ethiopia in which Shanchol™ was introduced through the public health system. The vaccination site was selected based on cholera cases reported in previous years. Social mobilization involved sensitization of community leaders, household visits, and mass distribution of banners, posters and leaflets. The vaccination was implemented after careful microplanning of logistics and cold chain, manpower, transportation, vaccine supply and supervision and monitoring of adverse events. Vaccine administration was recorded on individual vaccination cards. Vaccine delivery costs were collected and analyzed after vaccination. As there was no experience with Shanchol™ in Ethiopia, a bridging trial was conducted to demonstrate safety and immunogenicity of the vaccine in the local population prior to the mass vaccination. Oral cholera vaccination was conducted in two rounds of four days each in February 2015 and March 2015 in 10 selected villages of Shashemenae rural district of Ethiopia. A total of 62, 161 people targeted. 47, 137 people (76%) received the first dose, and 40, 707 (65%) received two doses. The financial cost of the vaccination campaign was estimated at US $2·60 per dose or US $5·64 per fully immunized person. The cost of vaccine delivery excluding vaccine procurement was $0·68 per dose or $1·48 per fully immunized person. The study demonstrates that mass cholera vaccination administered through the public health system in Ethiopia is feasible, can be implemented through the existing health system at an affordable cost, and the vaccine is acceptable to the community. The lessons from this study are useful for deploying OCV in other African endemic settings through the public health system and may guide future immunization policy decisions.